Lyman H. Howe's high class moving pictures - new magic pictures - Courier Co. litho., Buffalo, N.Y. (1898)
Motion picture poster for "Lyman H. Howe's high class moving pictures - new magic pictures" shows people watching motion picture in theater, includes insert of head-and-shoulders portrait of Lyman H. Howe.